The oldest record of Saurosphargiformes (Diapsida) from South China could fill an ecological gap in the Early Triassic biotic recovery - Cheng,Long; C. Moon,Benjamin; Yan,Chunbo; Motani,Ryosuke; Jiang,Dayong; An,Zhihui; Fang,Zichen (PeerJ, 2022)
Diversification following the end-Permian mass extinction marks the initiation of Mesozoic reptile dominance and of modern marine ecosystems, yet major clades are best known from the Middle Triassic suggesting delayed recovery, while Early Triassic localities produce poorly preserved specimens or have restricted diversity. Here we describe Pomolispondylus biani gen. et sp. nov. from the Early Triassic Nanzhang-Yuan’an Fauna of China assigned to Saurosphargiformes tax. nov., a clade known only from the Middle Triassic or later, which includes Saurosphargidae, and likely is the sister taxon to Sauropterygia. Pomolispondylus biani is allied to Saurosphargidae by the extended transverse processes of dorsal vertebrae and a low, table-like dorsal surface on the neural spine; however, it does not have the typical extensive osteoderms. Rather an unusual tuberous texture on the dorsal neural spine and rudimentary ossifications lateral to the gastralia are observed. Discovery of Pomolispondylus biani extends the known range of Saurosphargiformes and increases the taxic and ecological diversity of the Nanzhang-Yuan’an Fauna. Its small size fills a different ecological niche with respect to previously found species, but the overall food web remains notably different in structure to Middle Triassic and later ecosystems, suggesting this fauna represents a transitional stage during recovery rather than its endpoint.
Keywords: Early Triassic; Nanzhang-Yuan’an Fauna; Saurosphargiformes; Saurosphargidae; Marine reptile; End-Permian mass extinction; Ecosystem recovery